EVALUATION OF PHYSICAL EDUCATION, SPORTS AND HEALTH LEARNING IN SPECIAL SCHOOLS IN SOPPENG REGENCY, SOUTH SULAWESI PROVINCE - Uppy, uupriadi; Supriadi, Supriadi; Raharjo, Hermawan Pamot; Kusuma, Donny Wira Yudha (Universitas Negeri Semarang, 2025)
The background to this research is that the implementation of physical education, sports and health learning in special schools throughout Soppeng Regency is still not appropriate to the needs of children with special needs. The aim of this research is to evaluate the preparation, process and learning outcomes of physical education, sports and health in special schools in Soppeng Regency. This research is a mix mathods research and analyzes data using the Countenance Stake evaluation model. The population and sample in this study consisted of 6 school principals and 6 PJOK teachers. Data collection techniques in this research used instruments, observation, documentation, interviews and questionnaires. The results of this research show: (1) the preparatory (antecedent) stage of physical education, sports and health learning in special schools in Soppeng district is in the quite good category, (2) the process (transaction) stage of physical education, sports and health learning in special schools in all districts Soppeng is in the quite good category, (3) the results (outcomes) of physical education, sports and health learning in special schools throughout Soppeng Regency are in the quite good category.